SUBMARINE MASS MOVEMENT AND LOCALIZED TSUNAMI POTENTIALITY OF MENTAWAI BASIN, SUMATERA, INDONESIA - Haryadi Permana; C. Singh (BULLETIN OF THE MARINE GEOLOGY, 2010)
The new bathymetry and seismic data were acquired during the PreTI-Gap marine survey (February 15 to March 6, 2008). The survey was carried out along the NE margin of Mentawai Island using multi-beam swath bathymetry equipment, and 28-channels seismic streamer and four-airgun source. The first target was the Mega Island region near the epicenter of the 2007 great earthquake. The shallow bathymetry is characterized as a flat coral platform suggesting that 200 km elongated plateau is slowly subsiding without any active faults. Further north, from South Pagai to North of Siberut Islands, the seafloor morphology changes significantly. The deep and wide canyons or valleys produce very rough seafloor morphology between 50 and 1100 m water depth. In general, the submarine topography shows two break slopes at different depths. Between slope breaks, the undulating, hilly and circular features dominate, possibly caused by mass movement. A push-up ridge is observed that dams the sediments eroded within a steep slope northeastward side. The seismic reflection data acquired along 14 dip seismic lines at the NE flank of Mentawai Islands, from Siberut to the South of Pagai Islands. We observed a set of southwestward dipping back thrust bounding the NE margin of the Mentawai Island and the push-up ridge observed on bathymetric image, which suggest that Mentawai fault is not pure a strike slip fault, but consists of a set of back thrusts. Such kind of back thrust movement at the flank of Mentawai basin can trigger mass movement or landslide that can produce localized tsunami causing damages to Sumatera mainland such as Padang, Painan or northern Bengkulu provinces and Mentawai Islands. Therefore, it is important to re-design the tsunami warning system, especially in this region, in order to mitigate tsunami risk to coastal region of western Sumatera. Keywords: multi-beam swath bathymetry, 28-channels seismic streamer, seismic reflection, back thrust, mass movement or landslide, tsunami warning system, mitigate tsunami risk Data batimetri dan seismik baru telah didapatkan selama survey kelautan PreTi-Gap (15 Februari hingga 6 Maret 2008). Survei dilaksanakan sepanjang tepian timurlaut Kepulauan. Mentawai menggunakan peralatan multibeam batimetri, seismik saluran ganda 28 kanal dengan 4 sumber energi airgun. Sasaran pertama adalah memetakan kawasan perairan P. Mega dekat pusat gempa besar tahun 2007. Kenampakan batimetri dangkal dicirikan dengan adanya dataran paparan terumbu karang sepanjang 200km yang secara perlahan mengalami penurunan tanpa akifitas sesar. Lebih jauh ke utara dari P. Pagai Selatan sampai di utara P. Siberut, morfologi dasar laut memperlihatkan perubahan secara signifikan yaitu lembah dalam dan lebar membentuk morfologi dasarlaut yang kasar dengan beda kedalaman antara 50 hingga 1100 meter. Secara umum, topografi dasar laut memperlihatkan perhentian dua lereng pada kedalaman yang berbeda. Diantara batas lereng yang dicirikan adanya kenampakan perlipatan, perbukitan dan bentuk melingkar diperkirakan sebagai hasil gelinciran batuan/tanah. Punggungan terangkat yang teramati merupakan penahan endapan yang melongsor pada lereng curam pada sisi sebelah timurlaut. Sebanyak 14 lintasan sismik refleksi pada sayap bagian timurlaut Kepulauan Mentawai, dari P. Siberut hingga ke selatan P. Pagai. Patahan anjak belakang yang teramati dengan sudut kemiringan ke arah baratdaya memotong bagian tepian timurlaut dari Kepulauan Mentawai dan punggungan terangkat yang terekam pada peta batimetri menegaskan bahwa Patahan Mentawai bukan murni sebagai patahan geser mengkanan akan tetapi juga memiliki komponen patahan anjak belakang. Setiap pergerakan sesar anjak di sisi Cekungan Mentawai dapat memicu gerakan tanah atau longsoran bawah laut dapat membangkitkan tsunami lokal yang mengakibatkan kerusakan di daratan Sumatera seperti di Padang, Painan atau Propinsi Bengkulu bagian utara dan Kepulauan Mentawai. Oleh karena itu adalah sangat penting untuk merencanakan sistim peringatan tsunami khususnya di kawasan tersebut dengan tujuan untuk melakukan mitigasi resiko bencana tsunami di kawasan pantai barat Sumatera. Kata Kunci: multibeam batimetri, seismik saluran ganda 28 kanal, sismik refleksi, sesar anjak belakang, gerakan tanah atau longsoran, peringatan dini tsunami, mitigasi resiko tsunami